Self‐measured worksite blood pressure and its association with organ damage in working adults: Japan Morning Surge Home Blood Pressure (J‐HOP) worksite study - Tomitani, Naoko (J Clin Hypertens (Greenwich), 2020)
The effects of elevations in blood pressure (BP) on worksite stress as an out‐of‐office BP setting have been evaluated using ambulatory BP monitoring but not by self‐measurement. Herein, we determined the profile of self‐measured worksite BP in working adults and its association with organ damage in comparison with office BP and home BP measured by the same home BP monitoring device. A total of 103 prefectural government employees (age 45.3 ± 9.0 years, 77.7% male) self‐measured their worksite BP at four timepoints (before starting work, before and after a lunch break, and before leaving the workplace) and home BP in the morning, evening, and nighttime (at 2, 3, and 4 a.m.) each day for 14 consecutive days. In the total group, the average worksite systolic BP (SBP) was significantly higher than the morning home SBP (129.1 ± 14.3 vs. 124.4 ± 16.4 mmHg, p = .026). No significant difference was observed among the four worksite SBP values. Although the average worksite BP was higher than the morning home BP in the study participants with office BP < 140/90 mmHg (SBP: 121.4 ± 9.4 vs. 115.1 ± 10.4 mmHg, p < .001, DBP: 76.0 ± 7.7 vs. 72.4 ± 8.4 mmHg, p = .013), this association was not observed in those with office BP ≥ 140/90 mmHg or those using antihypertensive medication. Worksite SBP was significantly correlated with the left ventricular mass index evaluated by echocardiography (r = 0.516, p < .0001). The self‐measurement of worksite BP would be useful to unveil the risk of hypertension in working adults who show normal office and home BP.